Improving Critical Thinking Ability of Elementary School Students in Science Learning through Scientific Learning Model based on Tri Kaya Parisudha - I Ketut Suparya; Wartayasa, I Ketut; Ariyana, Komang Sesara (Universitas Pendidikan Ganesha, 2025)
Good critical thinking skills are absolutely necessary to form quality human beings according to global developments in the 21st century. In this regard, the purpose of this study is to describe the differences in critical thinking skills in grade V elementary school students between students who follow the scientific learning model based on tri kaya parisudha and students who follow learning with scientific models in science learning. This research is a quasi-experimental research, in this study involving two class groups, namely the experimental group and the control group. The experimental design used in this research is pretest-posttest nonequivalent control group design. Hypothesis testing was carried out with an uncorrelated t test using the N gain score. The results showed that there was a significant difference in the critical thinking skills of students who were taught using a scientific learning model based on tri kaya parisudha with students who were taught with a scientific learning model. This is evidenced from the calculation results obtained that the statistical value of F = 6.621 with a significance level smaller than 0.05. In other words, learning with a scientific model based on tri kaya parisudha is very effective for improving students' critical thinking skills.